Rational arguments for regulatory acceptance of consistency testing: benefits of non-animal testing over in vivo release testing of vaccines. (31st December 2023) - Hoefnagel, Marcel H.N.; Stickings, Paul; Smith, Dean; Jungbäck, Carmen; Van Molle, Wim; Tesolin, Lorenzo
ABSTRACT: Introduction: There are rational arguments to replace existing in vivo potency and safety assays for batch release testing of vaccines with more advanced non-animal techniques to measure critical quality attributes. However, the introduction of in vitro alternatives to replace in vivo release assays of authorized vaccines is challenging. Areas covered: This report describes the hurdles encountered in substituting in vivo assays and ways to overcome these and provides arguments why more advanced in vitro alternatives are superior, not only as a tool to monitor the quality of vaccines but also from a practical, economical, and ethical point of view. The rational arguments provided for regulatory acceptance can support a strategy to replace/substitute any in vivo batch release test if an appropriate non-animal testing strategy is available. Expert opinion: For several vaccines, in vivo release assays have been replaced leading to an optimized control strategy. For other vaccines, new assays are being developed that can expect to be introduced within 5–10 years. From a scientific, logistical, and animal welfare perspective, it would be beneficial to substitute all existing in vivo batch release assays for vaccines. Given the challenges related to development, validation, and acceptance of new methods, and considering the relatively low prices of some legacy vaccines, this cannot be done without government incentives and supportive regulatory authorities from all regions.